High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

Hemophagocytic lymphohistiocytosis in total parenteral nutrition dependent children: description of 5 cases and practical tips for management. - Pastore, Serena; Barbieri, Francesca; Di Leo, Grazia; Valencic, Erica; Tommasini, Alberto; Ventura, Alessandro (J Pediatr Hematol Oncol, 2014)
Although total parenteral nutrition (TPN) is mandatory in children with intestinal failure, this treatment is not risk free. The main complications of TPN include catheter-related sepsis, thrombosis, hepatic cholestasis and cirrhosis, metabolic bone disease, and, rarely, reactive hemophagocytic lymphohistiocytosis (HLH). The pathogenesis of HLH in patients with TPN is not known, although some authors hypothesized that it can result from the activation of macrophages because of "fat overload." We reported 5 cases of HLH that occurred in patients with 4 different underlying disorders, all requiring TPN for a long term. In our series, an underlying immunological defect or a serious infection (sepsis) can have triggered HLH. Therefore, it could be reasonable to hypothesize that besides TPN in itself, minor immune defects and infections may act together by overcoming a threshold of immune stimulation, which ultimately leads to HLH.
Keywords: Child, Preschool; Fatty Acids; Female; Humans; Infant; Intestinal Diseases; Lymphohistiocytosis, Hemophagocytic; Male; Parenteral Nutrition, Total; Steroids; Treatment Outcome

Hepatic glycogenosis in an adolescent with diabetes. - Bua, Jenny; Marchetti, Federico; Faleschini, Elena; Ventura, Alessandro; Bussani, Rossana (J Pediatr, 2010)
Keywords: Adolescent; Diabetes Mellitus, Type 1; Female; Glycogen Storage Disease; Humans; Liver Diseases